University and challenge of citizenship education. Professors’ conceptions in training - Pérez-Rodríguez, Noelia; de-Alba-Fernández, Nicolás; Navarro-Medina, Elisa (Frontiers in Education, 2022)
Society and, therefore, the university, as a public space, face the challenge of training a critical citizenry capable of confronting existing problems. The work we present here highlights the role played by university professors in this issue. By means of a multiple case study we delve into the conceptions of nine university teachers in training on their conceptions of citizenship, citizenship education and university. The approach to their conceptions allows us to establish a framework of interpretation that reflects different levels of progression in their conceptions, from simple to complex. The least elaborated conceptions correspond to a vision of citizenship of a legal nature, without explicit proposals on how to educate for citizenship and under a conception of a university whose purpose is to transmit contents. Those corresponding to more complex levels refer to a perception of citizenship of a democratic and transformative nature, where the key to educating citizenship is the introduction of controversial issues, under a conception of a university that is critical and connected to social reality. Between both extremes there are intermediate levels, as well as obstacles and facilitators that favor or impede the development of more complex conceptions. Their analysis is key to incorporating appropriate training strategies. The improvement of continuous teacher training in this area will have a direct impact on students’ citizenship skills.